Anti-Toxoplasma Gondii Antibody Seroprevalence Among Pregnant Women in Baghdad - Taghreed Khudhur Mohammed, Zena Kassem Khalil, Alaa Abdulkhaliq (Pakistan Journal of Medical & Health Sciences, 2022)
Millions of pregnancy abnormalities occur throughout the world every year, many of which go unnoticed or untreated. The parasite Toxoplasma gondii (T. gondii) causes sometimes this infection among expectant mothors. So, the current study’s goals are to evaluate the the anti-Toxoplasma IgG seroprevalence and anti-Toxoplasma IgM antibodies in pregnant women in Baghdad, as well as environmental, psychological, and behavioural factors associated with infection in women. A total of two hundred and twelve (212) pregnant Iraqi women who visited personal laboratories in Baghdad were collected. Their ages ranged from 18 to 33 years. They have all had repeated spontaneous miscarriages in the past. Sera samples were collected, and IgG and IgM levels were estimated for the study participants. 61 samples out of 212 sera examined were IgG-positive (28.8%), whereas 19 tested IgM-positive(42.4%). In (54%) of the IgG-positive patients and (3 % of the IgM cases), a history of spontaneous abortion was mentioned.while there was no significant difference in the seroprevalence of Toxoplasma IgM levels according to maternal age,the IgG levels were considerably higher(p 0.05) in older age groups.the findings showed that IgG seroprevalence tended to be lower in educated participants(11.8%) compared to the uneducated group(17%) (from primary school education up to university graduates). The majority of the study’s risk factors did not significantly correlated with the seroprevalence of anti-Toxoplasma IgG and IgM antibodies, However, there was a positive coerelation between untreated water sources, cat exposure and undercooked meat with the anti-Toxoplasma IgG and IgM antibodies. A conclusion can be made that untreated water, cat handling and undercooked meat increase the seroprevalence of anti- toxoplasma antibodies as the correlation reveals a positive relation between these parameters and the anti- toxoplasma antibodies. Keywords: anti- toxoplasma antibodies, IgM, IgG, Iraq.